Validation of the Modified Friedewalds Formula to Calculate Low-density Lipoprotein Cholesterol in Bangladeshi Population (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Objective: A modification of Friedewalds formula was proposed to calculate LDL cholesterol in Bangladeshi population up to serum triglyceride concentration of 1000 mg/dL. The aim of this study was to validate the modification of Friedewalds formula in Bangladeshi population.Methods: Serum total cholesterol, triglyceride, high-density lipoprotein cholesterol and low-density lipoprotein cholesterol concentrations were measured in specimens obtained form 314 adult Bangladeshi subjects selected conveniently. LDL cholesterol concentrations were also calculated by modified Friedewalds formula and original Friedewalds formula. Results were expressed as mean ± SD and calculated LDL cholesterol was compared with measured LDL cholesterol by two-tailed paired t test and Pearsons correlation coefficient (r).Results: The mean ± SD of measured LDL cholesterol was 138.3 ± 54.58 mg/dL. LDL cholesterol calculated by modified Friedewalds formula and original Friedewalds formula were 135.9 ± 59.26 mg/dL (P>0.05) and 123.5 ± 65.75 mg/dL (P